Forecasting inflation in China - Aaron Mehrotra; José R. Sánchez-Fung (Bank of Finland, Institute for Economies in Transition (BOFIT), 2008)
This paper forecasts inflation in China over a 12-month horizon. The analysis runs 15 alternative models and finds that only those considering many predictors via a principal component display a better relative forecasting performance than the univariate benchmark.
URN:NBN:fi:bof-201408072057
Keywords: 330